1995
DOI: 10.1007/bf00052169
|View full text |Cite
|
Sign up to set email alerts
|

Defensive and secondary metabolism in plant tissue cultures, with special reference to nicotinamide, glutathione and oxidative stress

Abstract: The purpose of the presentation is to interconnect and illuminate certain parts of metabolism regarding stress signalling and defensive functions, including secondary metabolism in intact plants and plant tissue cultures. Increased cell/tissue levels of reactive oxygen species like H202, 0 2 and .OH and the metabolism of glutathione, are linked to defensive/secondary metabolism and tissue differentiation. Special attention is paid to nicotinamide. A hypothetical role of nicotinamide and its metabolites as stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 77 publications
1
34
0
2
Order By: Relevance
“…This compound is the precursor to the essential coenzymes nicotinamide adenine dinucleotide (NAD) and nicotinamide adenine dinucleotide phosphate (NADP). These coenzymes facilitate many oxidation and reduction reactions in living cells, which include linking the TCA cycle and oxidative phosphorylation (Berglund and Ohlsson, 1995). In Symbiodinium, as in other primary producers, NADP + is a major acceptor of electrons in photosystem I, which in turn reduces the production of ROS (Takahashi and Murata, 2008).…”
Section: Organic Acids Intermediates and Antioxidantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This compound is the precursor to the essential coenzymes nicotinamide adenine dinucleotide (NAD) and nicotinamide adenine dinucleotide phosphate (NADP). These coenzymes facilitate many oxidation and reduction reactions in living cells, which include linking the TCA cycle and oxidative phosphorylation (Berglund and Ohlsson, 1995). In Symbiodinium, as in other primary producers, NADP + is a major acceptor of electrons in photosystem I, which in turn reduces the production of ROS (Takahashi and Murata, 2008).…”
Section: Organic Acids Intermediates and Antioxidantsmentioning
confidence: 99%
“…In Symbiodinium, as in other primary producers, NADP + is a major acceptor of electrons in photosystem I, which in turn reduces the production of ROS (Takahashi and Murata, 2008). In higher plants, nicotinamide has been identified as a signal molecule of DNA damage and oxidative stress, which facilitates a number of defence-related metabolic reactions (Berglund, 1994;Berglund and Ohlsson, 1995). A similar defence and signalling mechanism may also function in the cnidarian-dinoflagellate symbiosis, though this awaits confirmation.…”
Section: Organic Acids Intermediates and Antioxidantsmentioning
confidence: 99%
“…The H 2 O 2 level in the P medium was ninefold and fourfold that in the M and G media, respectively. It has been suggested that oxidative burst and secondary metabolism are closely related (Berglund and Ohlsson 1995;Zhao et al 2001). Despite a high level of oxidative stress, application of the P medium strategy not only produced high cell growth and high AQ but also produced superior antioxidant vitamin levels.…”
Section: Lipid Peroxidation and Antioxidant Vitaminsmentioning
confidence: 99%
“…It has been hypothesized that nicotinamide (NIC) and/or its metabolites nicotinic acid and N-methyl nicotinic acid (trigonelline; TRIG) may constitute a link between various types of stresses, especially stress causing DNA strand breaks, and the induction of defensive metabolism in eukaryotic cells [9][10][11][12]. An important source of NIC release in response to stress is the DNA strand break-activated eukaryotic enzyme poly(-ADP-ribose)polymerase (PADPRP) [13,14].…”
Section: Introductionmentioning
confidence: 99%